On-road measurements of NMVOCs and NOx: Determination of light-duty vehicles emission factors from tunnel studies in Brussels city center. (December 2015) - Ait-Helal, W.; Beeldens, A.; Boonen, E.; Borbon, A.; Boréave, A.; Cazaunau, M.; Chen, H.; Daële, V.; Dupart, Y.; Gaimoz, C.; Gallus, M.; George, C.; et al.
Abstract: Emission factors (EFs) of pollutants emitted by light-duty vehicles (LDV) were investigated in the Leopold II tunnel in Brussels city center (Belgium), in September 2011 and in January 2013, respectively. Two sampling sites were housing the instruments for the measurements of a large range of air pollutants, including non-methane volatile organic compounds (NMVOCs), nitrogen oxides (NOx ) and carbon dioxide (CO2 ). The NMVOCs and NOx traffic EFs for LDV were determined from their correlation with CO2 using a single point analysis method. The emission factor of NOx is (544 ± 199) mg vehicle −1 km −1 ; NMVOCs emission factors vary from (0.26 ± 0.09) mg vehicle −1 km −1 for cis-but-2-ene to (8.11 ± 2.71) mg vehicle −1 km −1 for toluene. Good agreement is observed between the EFs determined in the Leopold II tunnel and the most recent EFs determined in another European roadway tunnel in 2004, with only a slight decrease of the EFs during the last decade. An historical perspective is provided and the observed trend in the NMVOCs emission factors reflect changes in the car fleet composition, the fuels and/or the engine technology that have occurred within the last three decades in Europe. Highlights: Measurements of traffic-related pollutants during two tunnel experiments in Belgium. NMVOCs in the tunnel are dominated by compounds known to be traffic marker. Determination of NMVOCs traffic emission ratio from their correlation with CO2 . Observed emission factors agree well with the most recent European emission factors. Little changes in NMVOCs EF since 10 years.